2002
DOI: 10.1177/0011128702048001007
|View full text |Cite
|
Sign up to set email alerts
|

Values and Evaluation: Assessing Processes and Outcomes of Restorative Justice Programs

Abstract: Increased interest in the restorative justice programs is accompanied by concern for whether they work and through what basic processes. Yet the task of evaluating restorative justice programs is a daunting one because they are so diverse, pursuing unique and multiple objectives. Restorative justice is guided by values that emphasize healing and social well-being of those affected by crime. These values must guide program evaluation. The authors explore ways to conceptualize and measure program inputs and outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 49 publications
7
75
0
2
Order By: Relevance
“…This assertion calls for more research that examines the complicated interactions among participants, especially between adult victims and youths. Given the weaknesses of the current study's methodology, two types of research may deepen our understanding: (1) using ethnographic forms of qualitative research (e.g., participant observation during the conferences) with a more specified and guided research questions as well as longer observation period with increased number of interviews (Harris et al 2004;Presser and Van Voorhis 2002); and (2) longitudinal research to examine the transformative and preventive effects of restorative justice dialogue on victims as well as youths.…”
Section: Resultsmentioning
confidence: 99%
“…This assertion calls for more research that examines the complicated interactions among participants, especially between adult victims and youths. Given the weaknesses of the current study's methodology, two types of research may deepen our understanding: (1) using ethnographic forms of qualitative research (e.g., participant observation during the conferences) with a more specified and guided research questions as well as longer observation period with increased number of interviews (Harris et al 2004;Presser and Van Voorhis 2002); and (2) longitudinal research to examine the transformative and preventive effects of restorative justice dialogue on victims as well as youths.…”
Section: Resultsmentioning
confidence: 99%
“…Although 42.1% (n = 32) of the articles reviewed had some mention of restorative justice research, half of these simply identified the need for further studies to evaluate both long-and short-term effects. one study (Presser & VanVoorhis, 2002) provided program evaluation; one article detailed a pilot study for a restorative justice program (Helfgott, Lovell, Lawrence, & Parsonage, 2000); and Bradshaw and Umbreit (2003) offered a quantitative measurement tool to describe satisfaction with restorative justice practices. Clearly, social work research on restorative justice is conspicuous by its absence.…”
Section: An Overview Of Research On Restorative Justice In the Socialmentioning
confidence: 99%
“…Prior demographic research regarding participation in restorative justice practices determined Caucasian families are disproportionately represented in FGC in comparison to minority populations the process and impact of restorative justice practices. Presser and VanVoorhis (2002) articulated a primary impediment to research on restorative justice requires the evaluative researcher to be trained in restorative justice practices and principles. In order to fully capture and understand the subjective meaning, outcomes, and impact of restorative justice on a victim, offender, or community, Presser and VanVoorhis state the researcher must hold an insider's perspective on the process itself.…”
Section: An Overview Of Research On Restorative Justice In the Socialmentioning
confidence: 99%
“…Restorative justice and the victim's movement have gained increasing global recognition for its victim-orientation and goals of repairing harms and restoring harmony (Clear and Karp 1999;Immarigeon 1996;Presser and Voorhis 2002;Van Ness and Strong 1997). Stemming from this perspective and responding to limitations of existing criminological theories, Braithwaite (1989) proposed a theory of reintegrative shaming.…”
Section: Introductionmentioning
confidence: 99%